Electrical Impedance Myography in Dogs With Degenerative Myelopathy - Kowal, Joseph B.; Verga, Sarah A.; Pandeya, Sarbesh R.; Cochran, Randall J.; Sabol, Julianna C.; Rutkove, Seward B.; Coates, Joan R. (Frontiers in Veterinary Science, 2022)
Canine degenerative myelopathy (DM) leads to disuse and neurogenic muscle atrophy. Currently there is a lack of non-invasive quantitative measures of muscle health in dogs with DM. Muscle pathology has been previously quantified in other disorders using the technique of electrical impedance myography (EIM) but it has not been reported for DM. The objective of this study was to compare EIM between DM-affected and similar aged healthy dogs as well as assess EIM changes over time in DM-affected dogs. Multifrequency EIM was performed on DM affected dogs at baseline and during disease progression and on age-matched healthy dogs. Muscles evaluated in the pelvic limbs included the craniotibialis, gastrocnemius, gracilis, sartorius, and biceps femoris. The 100 kHz phase angle was extracted from the full frequency set for analysis. Phase values were lower in DM dogs as compared to healthy controls. Specifically, phase of the gastrocnemius was lower on the left (θ = 7.69, 13.06; p =0.002) and right (θ= 6.11, 11.72; p = 0.001) in DM versus control dogs, respectively. The mean phase value of all measured muscles was also lower on the left (θ = 9.24, 11.62; p = 0.012) and right (θ = 9.18, 11.72; p = 0.021). Other individual muscles measured did not reach statistical significance, although values were consistently lower in DM-affected dogs. With disease progression, downward trends in phase values were detected in DM-affected dogs when monitored serially over time. This study demonstrates that EIM 100 kHz phase values are sensitive to muscle pathology in DM and that phase values are decreased in dogs with DM. Measurements from the gastrocnemius muscle show the greatest differences from similar aged healthy dogs suggesting it may be the preferred muscle for future EIM studies.